2001
DOI: 10.1351/pac200173101599
|View full text |Cite
|
Sign up to set email alerts
|

Selective detection of neurotransmitters by fluorescence and chemiluminescence imaging

Abstract: In recent years, luminescence imaging has been widely employed in neurochemical analysis. It has a number of advantages for the study of neuronal and other biological cells: (1) a particular molecular species or cellular constituent can be selectively visualized in the presence of a large excess of other species in a heterogeneous environment; (2) low concentration detection limits can be achieved because of the inherent sensitivity associated with fluorescence and chemiluminescence; (3) low excitation intensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 78 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…It is released from neurons simultaneously with other neurotransmitters and acts as both a fast transmitter and a neuromodulator (Brown and Dale, 2002;Jo and Role, 2002;Newman, 2003;Santos et al, 1999Santos et al, , 2003Von Kugelgen et al, 1994;Wang and Yeung, 2001). In this work, we applied our ATP imaging scheme, which has to date only been employed with cultured astrocytes and endothelial cells, to the detection of ATP release in the ganglia of the freshwater snail Lymnaea stagnalis.…”
Section: Introductionmentioning
confidence: 99%
“…It is released from neurons simultaneously with other neurotransmitters and acts as both a fast transmitter and a neuromodulator (Brown and Dale, 2002;Jo and Role, 2002;Newman, 2003;Santos et al, 1999Santos et al, , 2003Von Kugelgen et al, 1994;Wang and Yeung, 2001). In this work, we applied our ATP imaging scheme, which has to date only been employed with cultured astrocytes and endothelial cells, to the detection of ATP release in the ganglia of the freshwater snail Lymnaea stagnalis.…”
Section: Introductionmentioning
confidence: 99%
“…The main absorption and emission properties of 5-HT in an aqueous solution involve the UV, near-UV spectral region [16]. Excitation and emission properties of 5-HT at longer wavelengths have been already reported that, despite their weak signal, were considered for an application of near-UV-visible fluorescence microscopy to the in situ imaging study of the uptake and depletion of neurotransmitters in astrocytes [17][18][19][20]. The application of multiphoton excitation showed the appearance of a broad emission band centered at 505 nm, as a result of indoleamine photoionization [21].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, this method was successfully applied to determine the glutamate content in rat plasma and serum samples. Since glutamate possesses few functional groups that can be exploited using conventional means of detection, enzymatic assay is an alternative approach to chemical derivatization procedures and produces a detectable analyte upon conversion of the substrate [3][4][5]. Typically, free enzymes are not stable for long time and their catalytic activities gradually decrease because of unfolding of its native structure caused by effects of heat and pH.…”
mentioning
confidence: 99%